Síntese, ensaios in vitro e estudos computacionais de aminoquinolinas possíveis inibidoras da cruzaína e rodesaína - Luan Carvalho Martins (2016)
In this work a series of aminoquinolines, potential inhibitors of cruzain and rhodesain, was synthesized, evaluated on in vitro assays and studied by in silico methods. Chagas disease is caused by Tripanossoma cruzi and about 8 million are estimated to be infected worldwide. Human African trypanosomiasis caused by Tripanossoma brucei is a major health problem in Africa. Current drugs used in treatment of both diseases shows high toxicity and low efficacy. Cysteine proteases cruzain and rhodesain, major proteases of T. cruzi and T. brucei respectively, are validated drug targets. A series of potential inhibitors of cruzain and rhodesain was planned based on a lead indolepyrimidine cruzain inhibitor (IC50 = 2.5 M). The synthesized series contains a 7chloro-4-aminoquinoline motif and various side chain lengths and basicity was explored. Sixteen compounds were prepared employing straightforward procedures with yields from 16% to 99%. Enzymatic assays showed that this series inhibited cruzain with CI50 as low as 13,2 M and rhodesain with IC50 as low as 33,3 M. The most potent cruzain inhibitor, aminoquinoline 20b, was found to be a competitive inhibitor. The activity of the compounds was evaluated in vitro against intracellular amastigotes T. cruzi and cytotoxicity on the normal fibroblast was evaluated. Among the compounds evaluated, three of them showed an IC50 lower than 50 µM, however low selectivity indexes were found. Docking studies against crystallographic structures of cruzain and rhodesain were conducted. The results of these studies suggest that the quinoline moiety can occupy the S2 pocket while the more flexible side chain can explore either S3 or S1 pockets. In order to gain further insight on binding mode of the aminoquinoline 20b, molecular dynamics were performed. The analysis of results suggests that the binding mode of this coumpound may differ from crystallographic binding modes of ligands containg similar groups. The results as a whole show that aminoquinolines may be a promising class in further investigations of cruzain and rhodeain inhibitors.